1991
DOI: 10.1300/j052v10n03_03
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Knowledge of Nurses in Long-Term Health Care Facilities

Abstract: Nurses practicing in long-term care facilities were surveyed on the adequacy of their nutrition education, nutrition knowledge, and general attitudes about the diet of elderly residents. While 78% of the 95 responding nurses reported taking a required nutrition course during their training, only 61% indicated the quantity of their nutrition education was sufficient and 66% indicated the quality of their education was sufficient. The mean nutrition knowledge score was 60% correct with 51 subjects scoring at thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
0
15
1
Order By: Relevance
“…There is no literature to compare these scores with for HSWs; however, research has been conducted on the nutritional knowledge of nurses with several indicating scores at least 10% higher than in the present study (Crogan & Shultz, 2000;Lindseth, 1997;Stanek et al, 1991;Vickstrom & Fox, 1976). A questionnaire by Stanek et al (1991) had a mean score of 60% correct among nurses, which is corroborated by several other studies. The higher scores of nurses compared with HSWs could be due to the requirement of higher education (i.e., a university degree), job requirements, and national regulations.…”
Section: Health Knowledge and Educational Needs Of Hswsmentioning
confidence: 67%
See 1 more Smart Citation
“…There is no literature to compare these scores with for HSWs; however, research has been conducted on the nutritional knowledge of nurses with several indicating scores at least 10% higher than in the present study (Crogan & Shultz, 2000;Lindseth, 1997;Stanek et al, 1991;Vickstrom & Fox, 1976). A questionnaire by Stanek et al (1991) had a mean score of 60% correct among nurses, which is corroborated by several other studies. The higher scores of nurses compared with HSWs could be due to the requirement of higher education (i.e., a university degree), job requirements, and national regulations.…”
Section: Health Knowledge and Educational Needs Of Hswsmentioning
confidence: 67%
“…Of the HSWs surveyed in the current study 97% were female with a mean age of 46 years, similar to profiles from various studies HC-HCCC, 1999). This mean age is somewhat higher compared to other health professionals, such as nurses, wherein the mean age is approximately 40 years (Stanek, Powell, & Betts, 1991). The majority (97%) of participants were Caucasian, which is high in contrast to most studies where 64% were reported to be Caucasian, and 10% visible minorities .…”
Section: Comparison Of the Demographic And Professional Characteristimentioning
confidence: 69%
“…Furthermore, Stanek et al. found that 60% of directors and staff nurses in nursing homes on average gave correct answers. The comparison with these studies supports the assumption that the questionnaire was truly complex and difficult to answer and that therefore the scoring approach used was a proper solution.…”
Section: Discussionmentioning
confidence: 99%
“…Stanek et al. developed a questionnaire by consulting a teaching guide on nutrition and pilot tested this questionnaire with 16 staff nurses. The final questionnaire was validated by two dieticians and the director of a nursing faculty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation